2021
DOI: 10.1073/pnas.2106690118
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of a disordered protein on its folded ligand

Abstract: Intrinsically disordered proteins often form dynamic complexes with their ligands. Yet, the speed and amplitude of these motions are hidden in classical binding kinetics. Here, we directly measure the dynamics in an exceptionally mobile, high-affinity complex. We show that the disordered tail of the cell adhesion protein E-cadherin dynamically samples a large surface area of the protooncogene β-catenin. Single-molecule experiments and molecular simulations resolve these motions with high resolution in space an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 78 publications
2
17
0
Order By: Relevance
“…Specifically, for a given set of solution conditions, sequences featuring uniform linear distributions of oppositely charged residues are predicted to favor more expanded conformations compared to sequences with identical amino acid compositions where the oppositely charged residues are segregated into distinct blocks along the linear sequence. These predictions made using simulation and theory ( 43 , 44 , 54 ) have been confirmed using different experiments ( 31 33 , 41 , 55 ).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Specifically, for a given set of solution conditions, sequences featuring uniform linear distributions of oppositely charged residues are predicted to favor more expanded conformations compared to sequences with identical amino acid compositions where the oppositely charged residues are segregated into distinct blocks along the linear sequence. These predictions made using simulation and theory ( 43 , 44 , 54 ) have been confirmed using different experiments ( 31 33 , 41 , 55 ).…”
supporting
confidence: 59%
“…Charged residues are key determinants of sequence–ensemble relationships of IDRs ( 19 , 39 41 ). They contribute through highly favorable free energies of hydration ( 42 ) and long-range electrostatic interactions.…”
mentioning
confidence: 99%
“…The presence of conserved positively charged islands on FRQ, and their role in FRH-binding, parallels work illustrating the importance of electrostatic interactions and multivalency in mammalian clock proteins and in other complexes comprising disordered proteins (Czarna et al, 2011;Holehouse, 2019;Ozber et al, 2010;Sherry et al, 2017;Tompa and Fuxreiter, 2008;Xu et al, 2015;Zhao et al, 2021). This pattern of multivalent electrostatic islands supports a fuzzy interaction model, where the proteins interact as a heterogeneous ensemble rather than a single fixed structure (Buljan et al, 2012;Sharma et al, 2015;Tompa and Fuxreiter, 2008;Wiggers et al, 2021). Relevantly, electrostatic interactions can increase the binding affinity between proteins in a fuzzy complex (Bugge et al, 2020;Shen et al, 2018;Wiggers et al, 2021).…”
Section: Discussionsupporting
confidence: 59%
“…This pattern of multivalent electrostatic islands supports a fuzzy interaction model, where the proteins interact as a heterogeneous ensemble rather than a single fixed structure (Buljan et al, 2012;Sharma et al, 2015;Tompa and Fuxreiter, 2008;Wiggers et al, 2021). Relevantly, electrostatic interactions can increase the binding affinity between proteins in a fuzzy complex (Bugge et al, 2020;Shen et al, 2018;Wiggers et al, 2021). This fuzzy complex model is further supported by evidence of a change in the conformational dynamics of the negative arm protein complex over the circadian day (Pelham et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…Some IDPs are devoid of any structure, even after binding to partners ( 15 ), but many are partially disordered (IPDP) and morph to accommodate their partners. Hence, efforts have focused on investigating their folding upon binding ( 6 , 10 , 16 18 ). These studies have shown that IPDPs bind partners via conformational selection (fold first and then bind) or induced-fit (bind first and fold while bound) processes.…”
mentioning
confidence: 99%